2011
DOI: 10.1371/journal.pone.0023317
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant VP1, an Akt Inhibitor, Suppresses Progression of Hepatocellular Carcinoma by Inducing Apoptosis and Modulation of CCL2 Production

Abstract: BackgroundThe application of viral elements in tumor therapy is one facet of cancer research. Recombinant capsid protein VP1 (rVP1) of foot-and-mouth disease virus has previously been demonstrated to induce apoptosis in cancer cell lines. Here, we aim to further investigate its apoptotic mechanism and possible anti-metastatic effect in murine models of hepatocellular carcinoma (HCC), one of the most common human cancers worldwide.Methodology/Principal FindingsTreatment with rVP1 inhibited cell proliferation in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 52 publications
2
29
0
Order By: Relevance
“…16 Several studies have shown that treatments targeting autophagy can modify the activation states of macrophages. 62,63,66,67,72 These findings should encourage studies to develop genetic and pharmacological approaches to skew TAM polarization to the M1 phenotype by targeting autophagy. For example, even if TLR2 deficiency causes a reduction of macrophage infiltration, this ablation also induces a significant suppression of autophagy and a reduction in the expression of TNF/ TNFα (tumor necrosis factor), IFNG (interferon, gamma) and CXCL2 (chemokine [C-X-C motif] ligand 2) in liver tissues, indicating an increase of M2 macrophage polarization, which in turn promotes hepatocarcinogenesis.…”
Section: The Significance Of Macrophage Autophagy For Cancermentioning
confidence: 94%
See 1 more Smart Citation
“…16 Several studies have shown that treatments targeting autophagy can modify the activation states of macrophages. 62,63,66,67,72 These findings should encourage studies to develop genetic and pharmacological approaches to skew TAM polarization to the M1 phenotype by targeting autophagy. For example, even if TLR2 deficiency causes a reduction of macrophage infiltration, this ablation also induces a significant suppression of autophagy and a reduction in the expression of TNF/ TNFα (tumor necrosis factor), IFNG (interferon, gamma) and CXCL2 (chemokine [C-X-C motif] ligand 2) in liver tissues, indicating an increase of M2 macrophage polarization, which in turn promotes hepatocarcinogenesis.…”
Section: The Significance Of Macrophage Autophagy For Cancermentioning
confidence: 94%
“…Inhibition of autophagy under these circumstances attenuates M2 macrophage polarization, which directly indicates that autophagy plays a key role in macrophage polarization. 67 Sorafenib is an antiangiogenic agent that has been approved for cancer treatment. However, some studies also demonstrated that antiangiogenic drugs may, in some conditions, accelerate cancer progression.…”
Section: Autophagy-mediated Control Of Macrophage Polarizationmentioning
confidence: 99%
“…This combination was also shown to induce an innate immune response involving monocytes/macrophages and NK cells, leading to prolongation of anti-metastatic effects [144][145][146] . CCL2 was also identified by Chen et al [147] as a potential target for development of future HCC treatment. Using the recombinant foot-and-mouth disease virus capsid protein VP1 (rVP1), they were able to induce apoptosis of HCC cell lines through deactivation of the AKT pathway and stimulation of caspase cascades via Bax.…”
Section: Livermentioning
confidence: 93%
“…Using the recombinant foot-and-mouth disease virus capsid protein VP1 (rVP1), they were able to induce apoptosis of HCC cell lines through deactivation of the AKT pathway and stimulation of caspase cascades via Bax. Furthermore, rVP1 downregulated the expression of CCL2 in an AKT-dependent manner, which can support the survival and migration of HCC tumor cell lines [147] . CXCR7, a CXCL12 receptor, has also been reported to be upregulated in HCC [148] .…”
Section: Livermentioning
confidence: 96%
See 1 more Smart Citation